Psychological Well-Being and Intrinsic Motivation: Relationship in Students Who Begin University Studies at the School of Education in Ciudad Real - González Olivares, Ángel Luis; Navarro, Óscar; Sánchez-Verdejo, Francisco Javier; Muelas, Álvaro (Frontiers in Psychology, 2020)
More and more studies and research have found a positive relationship between the participation of young people in altruistic activities and helping others, but it is interesting to discover a relationship of that personal and vocational satisfaction in the preparation and training in a profession as important to society as teaching. For students who begin university studies related to teaching, their psychological well-being and motivation towards this activity are very relevant aspects to consider. The access to and attainment of a University Degree with a great vocational character, such as that of Pre-School Teacher or Primary Education Teacher, can benefit the students who will be in charge. These future educational professionals will have adequate motivation and maintain a psychological well-being that, in short, will favour their personal balance and will impact their future students. This research aims to analyse the degree of psychological well-being and its relationship with the motivation towards starting the teaching career. A sample of 233 students and students aged between 17 or 19 years of age who are beginning university studies at the School of Education of Ciudad Real was selected. All participants are enrolled in the first year of the Degree in Pre-school and Primary Education. The relationship between the psychological well-being of the students and their motivation towards attaining a professional teaching career was analysed. Other variables such as age or sex were also taken into account. A quantitative study was carried out and the Ryff Psychological Welfare Scale and the Intrinsic Motivation Questionnaire (IMI) were used. Once the results were analysed, it was observed that there is a positive correlation between the perception of psychological well-being that the participants have and their motivation towards the beginning of university studies, whose professional focus is mainly direct teaching with the students of the early stages of Pre-school and Primary Education. There are also some significant differences, considering the age and sex of the participants. The vocational character of university preparation for the teaching profession may determine that students who begin their Degree studies have an important motivation towards the performance of their professional future.